(3GdJYde GdJfXjej hGdefXeI GdeJYdeI (B:s (3feGPL hJbfjGJ GdGOGQI aj YUQ GdeYQaI (B/s - (3YjThT, NjQIs ((3GdLRGFQ(B: s (3GdfTQ GdLGeYj GdLOjO(B, s, 2021)
(3eaghe GdefXeI GdeJYdeI hfXQjGJ GdJSjjQhGdfXQjGJ GdGbJUGOjI, hGdJWhQ GdJGQjNj deUWdM GdJYde, eY GdGfJbGd ef GdJYde GdaQOj Gdi GdJYde GdJfXjej, cPdc feGPL GfTGA hfbd GdeYQaI OGNd GdefXeI efgG fehPL ShSj hgjHQJ hHhGShQJ hSajdj, HGdGVGaI Gdi GdCSS heHGOF HfGA GdefXeGJ GdeJYdeI efgG GSJQGJjLjGJ GcJSGH GdfeGPL GdPgfjI hGdQDjI GdeTJQcI eY GcJSGH GdJMce GdTNUj ef NdGd hSGFd JSjjQ GdefXeGJ GdeJYdeI efgG GdJfXjejI hGdJcfhdhLjI hCNjQG HYV feGPL GdefXeGJ GdeJYdeI cfehPL SGfL heGQSjN heGQcQOhfehPL COdSf hLjeR heYhbGJ GdJMhd Gdi efXeI eJYdeI(B.s
(3eQGLY U(B. 175- 186s
Keywords: (3EOGQI(B- (3JfXjes; (3fXe GdeYdheGJs